ARDUINO BASED RADIO FREQUENCY IDENTIFICATION (RFID) APPLICATION FOR MOTORCYCLE SECURITY SYSTEM (xxxx-xxxx, 2025)
Vehicle security systems are essential in reducing and preventing theft, especially in densely populated areas where motorcycles are common targets. This study focuses on designing and implementing a motorcycle security system using Radio Frequency Identification (RFID) technology, integrated with an Arduino microcontroller. The proposed system replaces conventional ignition keys with RFID cards, allowing only authorized users to activate the engine. The study aims to evaluate the system’s effectiveness in improving motorcycle safety, particularly its ability to detect and respond to valid RFID tags. The research methodology includes identifying security issues, conducting a literature review, designing both hardware and software components, and testing the system’s performance. Performance indicators assessed include reading distance, reading angle, response time, and power efficiency. Experimental results show that the RFID system operates optimally at a reading distance of 2-5 cm, within a reading angle of 0-45 degrees, and with an average response time of 0.8 seconds. Overall, the system is proven to be effective, efficient, and reliable.Sistem keamanan kendaraan berperan penting dalam upaya pencegahan tindak pencurian, terutama pada sepeda motor yang sering menjadi sasaran. Penelitian ini bertujuan untuk merancang dan mengimplementasikan sistem keamanan sepeda motor berbasis teknologi Radio Frequency Identification (RFID) yang telah terintegrasi dengan mikrokontroler Arduino. Sistem ini menggunakan kartu RFID sebagai pengganti kunci konvensional untuk menghidupkan dan mematikan mesin secara otomatis, sehingga hanya pengguna yang memiliki kartu yang terdaftar yang dapat mengoperasikan kendaraan. Penelitian ini mengevaluasi efektivitas sistem dalam mencegah pencurian, serta utuk menguji kinerjanya pada berbagai kondisi. Metode penelitian yang digunakan mencakup identifikasi masalah, studi pustaka, perancangan perangkat keras dan lunak, serta pengujian performa sistem berdasarkan jarak baca, sudut baca, waktu respons, dan konsumsi daya. Hasil menunjukkan bahwa sistem mampu membaca kartu RFID pada jarak optimal 2-5 cm, sudut 0-45 derajat, dan waktu respons rata-rata 0,8 detik. Secara keseluruhan, sistem ini dinilai lebih efektif, efisien, dan andal dalam meningkatkan keamanan kendaraan.